Hubungan Kualitas Tidur dengan Kadar Gula Darah pada Usia Dewasa Muda Penderita Diabetes Melitus Tipe II di RSD Gunung Jati - Widi Febrianty; M. Iqbal Angga Kusuma; Esti Andarini (Asosiasi Riset Ilmu Kesehatan Indonesia, 2025)
Background: Type II Diabetes Mellitus is increasingly affecting young adults. Sleep quality is one of the factors influencing blood glucose levels. Poor sleep can impair glucose metabolism and worsen diabetic conditions. Objective: To determine the relationship between sleep quality and blood glucose levels among young adults with Type II Diabetes Mellitus at RSD Gunung Jati. Methods: This study used a quantitative approach with a cross-sectional correlational design. A total of 151 young adult respondents were selected using accidental sampling. Instruments included the Pittsburgh Sleep Quality Index (PSQI) questionnaire and a glucometer to assess sleep quality and blood glucose levels, respectively. Data were analyzed using the Spearman Rank test. Results: Statistical analysis showed a significant relationship between sleep quality and blood glucose levels, with a significance value of 0.001 (p < 0.05). Conclusion: There is a significant relationship between sleep quality and blood glucose levels among young adults with Type II Diabetes Mellitus. Good sleep quality plays a crucial role in diabetes management and glycemic control.